Mulheres na resistência: a participação nos grupos de luta armada no Brasil (1968-1971) - Chagas , Débora Campani (2022)
This work investigates the participation of some women in armed resistance groups that were constituted in opposition to the Brazilian military dictatorship. The groups selected for this study are: Revolutionary Marxist Political Workers Organization (Polop), Popular Revolutionary Vanguard (VPR), Revolutionary Armed Vanguard – Palmares (VAR-Palmares) and Oito de Outubro Revolutionary Movement (MR-8), with greater emphasis on RPV The women we investigated are Damaris Lucena, Dulce Maia, Iara Iavelberg, Jovelina Tonello, Maria do Carmo Brito, Renata Ferraz Guerra de Andrade, Sonia Lafoz, Tercina de Oliveira and Zenaide Machado. The sources are divided between documents from the repression, available in online archives, testimonies given by women, available online and in biographies books. News from newspapers of the time, available in digital media, and documentaries that also contain interviews granted by them, as well as an interview we conducted with Renata Guerra de Andrade. Our objectives were to investigate how this participation took place, in order to understand what tasks they performed, what was the perspective of revolution they wanted to build, and to what extent the organization of repression made it impossible to carry out this project, crossing not only the lives of militants, but also their families, through the State Terrorism policy.